TELAAH KRITIS ATAS LAPORAN KEUANGAN KOTA MADIUN - Taufik Kurrohman (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2011)
This research analysis the Madiun City’s financial reporting 2009. The author evaluate the development financial ability in Madiun City. The research object of this study is Madiun City’s Financial Report. The analysis development financial ability region is measured by budget and realize ratio. Finally, the result show that the realization of indirect expenditure in Madiun City is to low, the effects is some of people needed can’t be fullfil by local government. Keywords: financial reporting, budgeting, realization.